Yahudi Geleneğinde Aile: Tobit Kitabı Örneği/Family in Jewish Tradition: The Case of the Book of Tobit - Kübra Karagöz (Oksident, 2024)
In Judaism, the family plays a fundamental role in the spiritual development of the individual and the preservation of social identity. The family is the structure where religious teachings and cultural values are shaped and passed on to future generations. Judaism considers the teaching of religious and moral responsibilities by parents to their children as an indispensable duty for social continuity. The family, which has a central relationship with God, has been regarded as the strongest protector of identity and faith even during the diaspora periods. This reinforces the individual’s sense of identity and belonging, while also becoming a site of cultural resistance for the Jewish community. This theme, frequently encountered in Jewish tradition, is also present in the Book of Tobit. The Book of Tobit, significant for the continuity of culture and tradition for the diaspora Jews of the time, is a narrative that emphasizes the role of the family. With divine guidance, tradition, Judaism, death-rites, homeland, journey, exile, family, society, culture, belief, charity, goodness, and prayer at the forefront, the book is important for the continuity of Jewish identity. This study aims to examine the work within its historical and cultural context based on its literary language and content and to explain the concept of family in the Book of Tobit.